Changes in the plasma levels of myokines after different physical exercises in athletes and untrained individuals - Kapilevich L. V. Leonid Vladimirovich; Zakharova A. N. Anna; Kabachkova A. V. Anastasia; Kironenko T. A. Tatyana; Dyakova E. Yu. Elena; Orlov S. N. Sergey Nikolaevich (2017, 2017)
Title screen